Rate of incense usage in the northern part of Nigeria and its adverse effects among users - Rimi, Maryam Ibrahim; Abdulkadir, Saeed Suleiman; Jabbo, Astaharam Ardo; Yelwa, Ahmed Armiya’u (International Journal of Research in Medical Sciences, 2022)
Background: Incense is an oleoresin that seeps from wounds in the trunks and leaves of Boswellia trees (B. carterii and B. papyrifera, endemic to Arabia, Africa, China, and India, respectively). Incense is traditionally burned for a variety of home functions in different cultures, and it has been linked to airborne pigmented and depigmented dermatitis. Methods: Questionnaires were developed using SurveyHeart and administered to determine the rate of incense usage in some households in northern Nigeria. Responses were compiled, data collated and the findings showed that four hundred and sixty (460) people responded. Results: The highest age range that responded was between thirty to thirty-nine (30-39) years with forty-eight (48%). Seventy-three (73%) were married and about 62% have one to five (1-5) children. Ninety-five percent (95%) of them use incense bakhour to neutralize odour. The survey showed that most people have been using it for more than ten (10) years. The research also tells that most respondents burn about ten (10) grams daily. Majority of the respondents displayed no respiratory conditions as well as their family members while thirty-two (32%) claimed they and their families suffer some of respiratory ailment. Conclusions: In conclusion, the use of incense in the northern part of the country is on the high side (94.86% out of 460 respondents) both in frequency and dose-wise which poses as a serious health condition to its users due to the contents of the incense and approximately 68% of the respondents have no knowledge of its adverse effects.